Needs Analysis for Developing an Environmental Learning Model in an Environmental Knowledge Course - Eka Apriyanti; Abdul Gafur (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Environmental learning in Biology Education Study Programs plays an important role in developing the ecological competencies of prospective biology teachers. However, the Environmental Knowledge course continues to face challenges, including the dominance of theoretical instruction, limited integration of local environmental issues, and insufficient implementation of contextual and experiential learning activities, which may hinder students’ ability to connect environmental concepts with real-life phenomena. This study aims to analyze the need for developing an environmental learning model for the Environmental Knowledge course in the Biology Education Study Program. A descriptive quantitative survey method with a needs assessment approach was employed. The participants consisted of 85 Biology Education students selected through purposive sampling. Data were collected using a needs analysis questionnaire covering learning difficulties, preferred instructional methods, digital technology needs, and students’ expectations regarding environmental learning models. The data were analyzed using descriptive statistics, including frequencies, percentages, means, and standard deviations. The findings indicate that students had strong needs for contextual learning (92.8%), field-based activities (94.1%), strengthening environmental literacy (93.5%), collaborative learning (90.4%), and stronger connections between theory and practice (91.7%). Students also expressed a high need for the integration of digital technologies into environmental learning. The study concludes that the development of an environmental learning model should prioritize contextual, experiential, collaborative, digitally supported, and student-centered learning. This study contributes to environmental education and biology teacher education by providing empirical needs assessment evidence as a foundation for designing an environmental learning model aligned with the learning needs of prospective biology teachers.